An update on the role of thioredoxin-interacting protein in diabetic kidney disease: A mini review - Sun, Hong; Sun, Rong; Hua, Yulin; Lu, Qianyi; Shao, Xinyu (Frontiers in Medicine, 2023)
Thioredoxin-interacting protein (TXNIP) was first isolated from Vitamin D3-exposed HL60 cells. TXNIP is the main redox-regulating factor in various organs and tissues. We begin with an overview of the TXNIP gene and protein information, followed by a summary of studies that have shown its expression in human kidneys. Then, we highlight our current understanding of the effect of TXNIP on diabetic kidney disease (DKD) to improve our understanding of the biological roles and signal transduction of TXNIP in DKD. Based on the recent review, the modulation of TXNIP may be considered as a new target in the management of DKD.